The propargyl rearrangement to functionalised allyl-boron and borocation compounds - Wilkins, Lewis C.; Wieneke, Philipp; Rominger, Frank; Hashmi, A. Stephen K.; Hansmann, Max M. (Chemistry - a European journal, 2016)
A diverse range of Lewis acidic alkyl, vinyl and aryl boranes and borenium compounds that are capable of new carbon-carbon bond formation through selective migratory group transfer have been synthesised. Utilising a series of heteroleptic boranes [PhB(C6F5)2 (1), PhCH2CH2B(C6F5)2 (2), and E-B(C6F5)2(C6F5)C=C(I)R (R=Ph 3 a, nBu 3 b)] and borenium cations [phenylquinolatoborenium cation ([QOBPh][AlCl4], 4)], it has been shown that these boron-based compounds are capable of producing novel allyl- boron and boronium compounds through complex rearrangement reactions with various propargyl esters and carbamates. These reactions yield highly functionalised, synthetically useful boron substituted organic compounds with substantial molecular complexity in a one-pot reaction.
Gesehen am 25.08.2017